Reflection and transmission in non-local couple stress micropolar thermoelastic media - Deepa Gupta; Sangeeta Malik; Krishan Kumar; Raj Kumar Sharma (Zielona Góra: Uniwersytet Zielonogórski)
We have studied the problem of homogenous, isotropic non-local couple stress micropolar thermoelastic solid in the absence of body forces, couple density and heat resources. The reflection and transmission of waves at the interface of two distinct media have been investigated. It is observed that amplitude ratios of various reflected and transmitted waves are functions of wave number of incident waves and are affected by the non-local parameter of thermoelastic solid.
Keywords: non-local; thermoelastic solid; amplitude ratios; reflection; transmission; couple stress; wave number